1999
DOI: 10.1029/1998jb900072
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of subduction at Atlantic‐type margins: Insights from laboratory experiments

Abstract: Abstract. We have performed scaled lithospheric experiments to simulate the behavior of a ocean-continent plate system subjected to compressional strain over a geological timescale. Experiments have been constructed using sand and silicone putty, representing the brittle upper crust and the ductile lower crust/upper mantle, respectively; the layers floated on glucose syrup simulating the asthenosphere. Compressional stress is achieved by displacing a piston at constant velocity perpendicular to the plate margi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
141
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(154 citation statements)
references
References 85 publications
13
141
0
Order By: Relevance
“…Two main forces must be overcome to allow subduction to develop: elastic plate flexure (bending stress) and frictional resistance across a pre-existing fault (McKenzie, 1977). In our case study, although the slow convergence rate is not favoring a spontaneous subduction nucleation at the continent-ocean transition ( [Faccenna et al, 1999] and [Stern, 2004]), the sediment loading acting on a young lithosphere may provide an effective mechanism to enhance this process (Cloetingh et al, 1982). Similar case studies of Plio-Quaternary inversion of a former backarc basin can be found in the Japan sea (e.g.…”
Section: Mechanisms Of Subduction Inception and Tectonic Stylesupporting
confidence: 50%
See 1 more Smart Citation
“…Two main forces must be overcome to allow subduction to develop: elastic plate flexure (bending stress) and frictional resistance across a pre-existing fault (McKenzie, 1977). In our case study, although the slow convergence rate is not favoring a spontaneous subduction nucleation at the continent-ocean transition ( [Faccenna et al, 1999] and [Stern, 2004]), the sediment loading acting on a young lithosphere may provide an effective mechanism to enhance this process (Cloetingh et al, 1982). Similar case studies of Plio-Quaternary inversion of a former backarc basin can be found in the Japan sea (e.g.…”
Section: Mechanisms Of Subduction Inception and Tectonic Stylesupporting
confidence: 50%
“…Therefore passive margins are good potential locations for such a process to occur (e.g. [Cloetingh et al, 1982], [Faccenna et al, 1999] and [Leroy et al, 2004]; and references therein). Two main forces must be overcome to allow subduction to develop: elastic plate flexure (bending stress) and frictional resistance across a pre-existing fault (McKenzie, 1977).…”
Section: Mechanisms Of Subduction Inception and Tectonic Stylementioning
confidence: 99%
“…A parallel implication of our observations and interpretations is that far-field forces may perhaps not be able to propagate very deeply into a hyperextended continental margin. The resolution of contrasting oceanward-directed continental and landward-directed oceanic GPE against the TB and the hyperextended distal domain may perhaps ultimately localize as oceanic-continent subduction (e.g., Masson et al, 1994;Faccenna et al, 1999;Péron-Pinvidic et al, 2008;Marques et al, 2013;Redfield & Osmundsen, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, much of the distal domain can potentially comprise a permanently weakened zone (Masson et al, 1994;Faccenna et al, 1999;Péron-Pinvidic et al, 2008Mohn et al, 2010;Lundin & Doré, 2011;Sutra & Manatschal, 2012;Redfield & Osmundsen, 2013; this paper).…”
Section: The Extended Marginmentioning
confidence: 99%
“…Davy and Cobbold (1988);Faccenna et al (1999); Guillaume et al (2009);Duarte et al (2013)). By adding fine iron powder (Funiciello et al, 2004;Schellart, 2008; sample h R σ r Newtonian Power-law rs Figure 3: Schematic rheometer setup, with gap height h and disk radius R, including a schematic depiction of shear stress σ variation as function of radial distance r for Newtonian and power-law materials, rs is the radial distance where the shear stress curves of Newtonian as well as power-law materials intersect (Carvalho et al, 1994).…”
Section: Iron Powdermentioning
confidence: 99%